AB0655 Ultrasound b-lines in the evaluation of interstitial lung disease in patients with systemic sclerosis: cut-off point definition for the presence of pulmonary fibrosis. (15th June 2017) - Tardella, M; Carlo, M Di; Carotti, M; Filippucci, E; Grassi, W; Salaffi, F
Abstract : Background: Although in Systemic Sclerosis (SSc) the cutaneous manifestations are the most noticeable features, lung involvement guides the disease prognosis. High resolution computed tomography (HRCT) is the mainstay for the detection of the interstitial lung disease (ILD). However, exposure to ionising radiation is a major limitation for the repetition of this examination. Over the last years, lung ultrasound (US) gained an intriguing potential in the evaluation of several pulmonary condition, and in previous studies was found a significant correlation between US score and HRCT score [1]. Objectives: To establish the cut-off point of the US B-lines number for detecting the presence of SSc-ILD. Methods: Patients with SSc-ILD underwent chest HRCT, lung US, pulmonary function test, and clinical assessment. Exclusion criteria were represented by the presence of a coexisting congestive heart failure and other lung or pleural diseases (i.e., pneumonia, pleural effusion). HRCT were scored for the presence of ILD by an experienced radiologist, in accordance with the Warrick method. US assessment was performed by a US skilled rheumatologist, blinded to the HRCT results, and included the bilateral evaluation of 14 lung intercostal spaces (LIS) [2]. In each LIS the number of B-lines was recorded and summed. To test discriminant validity we used the receiver operating characteristic (ROC) curve analysis applying a Warrick score of 7 as external criterion for the presence of SSc-ILD. Results: Forty patients completed the study. The US B-lines number and the Warrick score confirmed an excellent correlation (Spearman's rho: 0.819, p<0.001). The ROC curve analysis revealed that the presence of 10 US B-lines is the cut-off point with the greatest positive likelihood ratio (12.52) for the presence of SSc-ILD (Table). Conclusions: The detection of 10 B-lines is highly predictive for the HRCT presence of SSc-ILD. In SSc patients, a lung US follow-up can optimize the employment of chest HRCT. Disclosure of Interest: None declared